1995
DOI: 10.1111/j.1365-277x.1995.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of elderly demented hospital residents

Abstract: The purpose of this study was to determine the effects of a dietary supplement (Fortisip, Cow & Gate Ltd) on the body weight, triceps skinfold thickness and mid‐arm muscle circumference of low weight, elderly, demented hospital residents. The height and weight of all residents (n = 293) of the Care of the Elderly wards of a large psychiatric hospital were measured, and body mass index (BMI) calculated for each individual. Forty‐six underweight residents (BMI 15.1–19.9) were matched by age, sex and BMI and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 14 publications
0
44
0
3
Order By: Relevance
“…Stage of dementia varied from mild to severe but was not specified in all studies. Mean BMI ranged between 20 and 25 kg/m 2 and only one study was restricted to malnourished patients (BMI < 20 kg/m 2 ; [165]). ONS provided between 125 and 680 kcal per day and were generally offered between meals, mainly in the morning.…”
mentioning
confidence: 99%
“…Stage of dementia varied from mild to severe but was not specified in all studies. Mean BMI ranged between 20 and 25 kg/m 2 and only one study was restricted to malnourished patients (BMI < 20 kg/m 2 ; [165]). ONS provided between 125 and 680 kcal per day and were generally offered between meals, mainly in the morning.…”
mentioning
confidence: 99%
“…In tubefed demented elderly patients, two studies reported weight gain [19,20], but two others reported no change [14,21]. Available trials regarding the effects of ONS [16,17] or TF [21,22] on functional status report no improvement. In terms of survival, most studies show no benefit [22][23][24].…”
Section: Ethical Considerations In Decisions On Active Enteral Nutritmentioning
confidence: 98%
“…Some studies on oral nutrition support (ONS) have shown improvements in body weight [16][17][18]. In tubefed demented elderly patients, two studies reported weight gain [19,20], but two others reported no change [14,21].…”
Section: Ethical Considerations In Decisions On Active Enteral Nutritmentioning
confidence: 99%
“…The studied nucleotides are primary units of nucleic acids consisting of a cycling nitrogenous base (purine or pyrimidine), a pentose sugar, and at least one phosphate group [2]. They possess similar chemical structures differing in the purinic or pyrimidinic base or in several substituents, requiring a highly efficient and selective analytical method for their separation.…”
Section: Nano-lc Separationmentioning
confidence: 99%
“…However, they become fundamental when the endogenous supply is not appropriate especially during pediatric growth or after their injury. Breast milk, with its unique composition, is considered to be the best source of nucleotides that have beneficial effects in infants, upon the immune system, small intestinal growth and development, lipid metabolism, and hepatic function [1][2][3][4]. Although not essential dietary nutrients, it has been demonstrated that supplementation of pediatric formulas with nucleotides is of benefit in neonatal nutrition for improving the immuno and protective responses [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%